Catalytic Methane Decomposition on In Situ Reduced FeCo Alloy Catalysts Derived from Layered Double Hydroxides - Dianfeng Cao; Yuwen Li; Chao Lv; Yongtao An; Jiangfeng Song; Mingcan Li; Xin Zhang (Nanomaterials, 2024)
Catalytic methane decomposition (CMD) reaction is considered a promising process for converting greenhouse gas CH4 into hydrogen and high-value-added carbon materials. In this work, a series of Al2O3-supported FeCo alloy catalysts were successfully prepared in the CMD process. Compared to the pre-reduced catalysts, the in situ reduced FeCo alloy catalysts showed higher methane conversion rates, with the highest reaching 83% at 700 °C, due to the finer active nanoparticle size and greater exposure of active site. Furthermore, the time-on-stream tests demonstrated that the catalytic activity of in situ reduced FeCo alloy catalysts could remain above 92.3% of the highest catalytic activity after 10 h. In addition, TEM analyses of the carbon products from the CMD in situ reduced catalysts revealed the production of carbon nanofibers and nanotubes several microns in length after the reaction. This indicates that the in situ reduced FeCo alloy catalysts more effectively promoted the growth of carbon nanofibers. These results could provide a viable strategy for future methane decomposition development aimed at producing hydrogen and high-value carbon.